The Effectiveness of e-Booklet on Female Sex Workers’ Knowledge and Behaviour of HIV/AIDS Prevention in Semarang - Nabilla Angel Sukma Wati; Nila Titis Asrining Tyas (International Journal Of Health Science, 2025)
Sex workers (FSW) are a key population at high risk of HIV/AIDS because they work frequently serving guests. HIV prevention knowledge and behavior are not optimal, education using the e-booklet "Mencegah HIV/AIDS Pada PSP" is a solution to improve HIV/AIDS prevention knowledge and behavior with direct media, easy to understand and accessible to sex workers. The study aims to determine the effectiveness of education using the e-booklet "Mencegah HIV/AIDS Pada PSP" on HIV/AIDS prevention knowledge and behavior among female sex workers (FSW) in Semarang Regency. Using quantitative, Quasi-experimental research design one sample group pre-test and post-test design. Samples of 62 respondents, consecutive sampling technique. Data collection using a questionnaire on HIV/AIDS prevention knowledge and behavior among female sex workers (FSW). Data were tested with Marginal Homogeneity. Results Before education, 62 respondents had poor knowledge and behavior of HIV/AIDS prevention and after education, 62 respondents had good knowledge and behavior of HIV/AIDS prevention. The Marginal Homogeneity Test shows a p-value of 0.000 (<0.05) so H1 is accepted and H0 is rejected, there is effectiveness of education using the e-booklet "Mencegah HIV/AIDS Pada PSP" on knowledge and behavior of HIV/AIDS prevention in female sex workers (FSW) in Semarang Regency. The results indicated a notable improvement in both knowledge and behavior among the participants. Prior to the intervention, participants exhibited poor knowledge and behaviors regarding HIV/AIDS prevention. However, after engaging with the e-booklet, there was a significant shift, with all 62 respondents showing improved knowledge and behavior. The statistical analysis using the Marginal Homogeneity Test yielded a p-value of 0.000 (<0.05), confirming the effectiveness of the education provided through the e-booklet.